SiRNA‐mediated NCAM1 gene silencing suppresses oxidative stress in pre‐eclampsia by inhibiting the p38MAPK signaling pathway. Issue 11 (28th July 2019) - Zhang, Xiao‐Lin; Xu, Feng‐Xian; Han, Xiao‐Yun
Abstract: Pre‐eclampsia (PE), whose pathophysiology and etiology remain undefined, represents a leading consequence of fetal and maternal mortality and morbidity. Oxidative stress (OS) is recognized to involve in this disorder. In this study, we hypothesized that neural cell adhesion molecule 1 (NCAM1) gene silencing would suppress the OS in the pregnancy complicated by PE. Initially, clinical samples were collected for determination of NCAM1 expression in placental tissues and levels of OS products in blood. To assess the regulatory mechanism of NCAM1 knockdown on OS, we used small interfering RNA (siRNA) to silence NCAM1 expression in human umbilical vein endothelial cells (HUVECs). Next, cells were treated with or without hypoxia/reoxygenation to observe the level changes of OS products and p38 mitogen‐activated protein kinase (p38MAPK) pathway‐related genes. Finally, an evaluation of HUVEC migration and invasion abilities was conducted by wound‐healing and transwell assays. Placenta of pregnancy with PE presented significantly increased NCAM1 expression in comparison to placenta of normal pregnancy. Meanwhile, enhanced OS in blood of pregnant women with PE was observed relative to women with normal pregnancy. siRNA‐mediated knockdown of NCAM1 gene could inhibit the p38MAPK signaling pathway, repress OS, and promote cell migration and invasion in HUVECs, indicating that NCAM1 inhibition could reduce the influence of PE. Importantly, blocking the p38MAPK signaling pathway reversed the inhibitory role of NCAM1 gene silencing on PE. Collectively, this study defines potential role of NCAM1 gene silencing as a therapeutic target in PE through inhibiting OS and enhancing HUVEC migration and invasion by disrupting the p38MAPK signaling pathway. Abstract : This study defines potential role of neural cell adhesion molecule 1 gene silencing as a therapeutic target in pre‐eclampsia through inhibiting oxidative stress and enhancing human umbilical vein endothelial cells migration and invasion by disrupting the p38 mitogen‐activated protein kinase signaling pathway.